2010
DOI: 10.1016/s0917-2394(10)70203-2
|View full text |Cite
|
Sign up to set email alerts
|

Mixed dentition space analysis in Egyptian children

Abstract: This study was done to examine the applicability of the Tanaka and Johnston and Moyers' methods of prediction in Egyptian population and to develop a new prediction method for this specific population if necessary. A total of 325 Egyptian students 145 female, 180 male, mean age 14.4 years, SD±1.1 years were randomly selected from 10 preparatory and secondary schools in Mansoura city, Dakahlia governorate, Egypt during the academic year 2008-2009. The mesiodistal crown diameters of the permanent teeth were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 22 publications
5
15
1
Order By: Relevance
“…These findings are similar to those reported previously for several ethnic backgrounds. [101113172223] This supports the conclusions of Buwembo and Luboga's[12] meta-analysis that mixed dentition analyses cannot be universally applied. However, the literature currently lacks studies that examine the clinical significance of the errors of tooth size prediction.…”
Section: Discussionsupporting
confidence: 76%
“…These findings are similar to those reported previously for several ethnic backgrounds. [101113172223] This supports the conclusions of Buwembo and Luboga's[12] meta-analysis that mixed dentition analyses cannot be universally applied. However, the literature currently lacks studies that examine the clinical significance of the errors of tooth size prediction.…”
Section: Discussionsupporting
confidence: 76%
“…The r and r 2 in our study was 0.57 and 0.25, respectively [Table 3]. These values are in agreement with the values reported in the study by Agarwal et al .,[1] and are higher than those reported in the studies by Jaroontham and Godfrey[15] (0.29 and 0.34), Durgekar and Naik[11] (0.56 and 0.25 r 2 ), and Hammad and Abdellatif[4] (0.78 and 0.89 in male and 0.63 and 0.87 in female, respectively).…”
Section: Discussionsupporting
confidence: 93%
“…[1] Different studies have shown the variations in prediction and regression equation to evaluate unerupted teeth. [1341112]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations